Serum amyloid A is a potential predictor of prognosis in acute ischemic stroke patients after intravenous thrombolysis - Chang, Qi; Li, Yaqiang; Xue, Min; Yu, Chuanqing; He, Jiale; Duan, Xun (Frontiers in Neurology, 2023)
Objectives Inflammation shows a notable relationship to acute ischemic stroke’s (AIS) occurrence and prognosis. However, existing research has confirmed that serum amyloid A (SAA) is an inflammatory biomarker. The aim of this paper was to investigate the association between SAA and the three-month clinical results of acute AIS patients after intravenous thrombolysis (IVT). Methods The evaluation of AIS patients with complete medical records was carried out by prospectively investigating patients hospitalized in our department between January 2020 and February 2023. The SAA levels were examined with the use of an immunosorbent assay kit that shows a relationship with the enzyme (Invitrogen Corp). Patients were dichotomized into favorable (mRS score of 0, 1 or 2) and unfavorable (mRS score of 3, 4, 5, or 6) results with the use of the modified Rankin Scale (mRS). Results A total of 405 AIS patients who were subjected to IVT therapy were prospectively covered. To be specific, 121 (29.88%) patients had an unfavorable prognosis during the follow-up for 3 months. On that basis, patients achieving unfavorable results gained notably greater SAA levels (39.77 (IQR 38.32–46.23) vs.31.23 (IQR 27.44–34.47), p < 0.001) during hospitalization in comparison to patients with a better result. In the analysis with multiple variates, SAA was adopted to achieve the independent prediction of the three-month unfavorable clinical results of acute AIS patients after IVT [OR:2.874 (95% CI, 1.764–4.321), p < 0.001]. When the fundamental confounding factors were regulated, the odds ratio (OR) of unfavorable prognosis after AIS patients undergoing IVT therapy was 4.127 (95% CI = 1.695–10.464, p = 0.032) for the maximum tertile of SAA in terms of the minimal tertile. With an AUC of 0.703 (95% CI, 0.649–0.757), SAA revealed a notably more effective discriminating capability in terms of CRP, NLR, EMR, and WBC. SAA as a predictor in terms of the prediction of three-month unfavorable results after AIS patients undergoing IVT therapy achieved specificity and sensitivity of 84.45% and 77.23%, as well as an optimal cut-off value (COV) of 37.39. Conclusion SAA level that is up-regulated during hospitalization is capable of serving as an effective marker in terms of the prediction of unfavorable three-month results in AIS patients after IVT.